Pandangan Terhadap Perubahan Persempadanan Bahagian Pilihan Raya di Kawasan Parlimen Hulu Langat dan Serdang, Selangor: Perceptions on the Change of Electoral Boundaries in Hulu Langat and Serdang Parliamentary Constituencies, Selangor - Besar, Junaidi Awang; Mohd Fauzir, Handika Wira; Abd Razak, Mohd Rodzi; Mohd Yusof, Ahmad Rizal (GEOGRAFI, 2017)
General election Malaysia has made Malaysia a country that practices parliamentary democracy and one of the elements in the election is the delimitation of the constituency. The purpose of the delimitation of constituencies was to compensate for the increase in population cast ballots in each district. However, the proposed of redistrict will be conducted in 2016 is still being discussed and will definitely have an impact on the environment, whether good or bad. Thus it is the purpose of this study to analyse voter perception about the changing of the delimitation of constituencies in 2016 in the Hulu Langat and Serdang, Selangor. This study using the questionnaire in court against 300 respondents respectively 150 respondents of voting ie aged 21 years and above in the Hulu Langat and Serdang and reference source secondary. The findings show that the respondents are aware of the consequences of the change in the borders that will be carried out in the year 2016 due to their respective rights and interests. They are aware that boundary changes that will be carried out will not only benefit the side, but should be fair in every factor and issue. Hence, voters need to be given information on the best delineation and their role to give an opinion should be taken into consideration by the EC to ensure the decision on the delimitation is beneficial to all parties.